2004
DOI: 10.1086/422886
|View full text |Cite
|
Sign up to set email alerts
|

Angular Clustering of Galaxies at 3.6 Microns from theSpitzerWide‐area Infrared Extragalactic (SWIRE) Survey

Abstract: We present the first analysis of large-scale clustering from the Spitzer Wide-area Infrared Extragalactic legacy survey (SWIRE). We compute the angular correlation function of galaxies selected to have 3.6 m fluxes brighter than 32 Jy in three fields totaling 2 deg 2 in area. In each field we detect clustering with a high level of significance. The amplitude and slope of the correlation function is consistent between the three fields and is modeled as w( ) ¼ A 1À with A ¼ (0:6 AE 0:3) ; 10 À3 ; ¼ 2:03 AE 0:10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 25 publications
4
25
1
Order By: Relevance
“…However, they provide sufficient information to compare the properties of different subsets of our data. The clustering amplitude for the full 10σ ADF-S 90 μm sample is equal to 1.1 × 10 −3 with the slope γ = 2, which is not very different from that found for other infrared galaxy surveys, for example SWIRE (Oliver et al 2004;de la Torre et al 2007). In case of the 6σ catalog, we observe a lower clustering amplitude for the Identified sources are shown as small stars.…”
Section: Correlation Functionmentioning
confidence: 44%
“…However, they provide sufficient information to compare the properties of different subsets of our data. The clustering amplitude for the full 10σ ADF-S 90 μm sample is equal to 1.1 × 10 −3 with the slope γ = 2, which is not very different from that found for other infrared galaxy surveys, for example SWIRE (Oliver et al 2004;de la Torre et al 2007). In case of the 6σ catalog, we observe a lower clustering amplitude for the Identified sources are shown as small stars.…”
Section: Correlation Functionmentioning
confidence: 44%
“…This expectation already has some observational evidence; for example, in the local Universe, selecting galaxies at 2.15 µm (K s band) from the Two Micron All Sky Survey (2MASS, Maller et al 2005), it is found that these galaxies are more clustered than those selected at optical wavelengths, with an angular correlation amplitude several times larger than found in the Sloan Digital Sky Survey Early Data Release (SDSS EDR, Connolly et al 2002). At higher redshifts, Oliver et al (2004), using Spitzer data, found that at z median 0.75 the correlation length of (m 3.6 ) AB < 20.1 (or equivalently K Vega < 18.7) selected galaxies is r 0 = 4.4 ± 0.1 h −1 Mpc with an angular correlation amplitude ∼60 times lower than for 2MASS local galaxies, and recent work has shown that more infrared-luminous galaxies are even more strongly clustered (Farrah et al 2006).…”
Section: Introductionmentioning
confidence: 84%
“…From ISO deep surveys, Matsuhara et al (2000) and Lagache and Puget (2000) performed a power spectrum analysis of the diffuse far-infrared (FIR) background and discovered fluctuations due to the large-scale clustering of dusty galaxies. Subsequently, angular clustering analyses of Spitzer surveys have been published (e.g., Oliver et al, 2004;de la Torre et al, 2007;Gilli et al, 2007;Magliocchetti et al, 2008). These works are mainly based on mid-infrared (MIR) data, but thanks to Herschel, recently, results from longer wavelengths have been gradually reported (e.g., Cooray et al, 2010;Maddox et al, 2010;Amblard et al, 2011;Magliocchetti et al, 2011;Planck Collaboration et al, 2011).…”
Section: Introductionmentioning
confidence: 99%